Journal of the American Society for Information Science (JASIS) - American Society for Information Science. (John Wiley & Sons, 1970)
Continues: American documentation, ISSN 0096-946X.Continued by: Journal of the American Society for Information Science and Technology, ISSN 1532-2882.